لهجة منطقة سطيف من خلال الممارسات اللغوية لدى الفئة المسنة ( قراءة في النظام المعجمي): The dialect of the Setif region through the linguistic practices of the elderly population (Reading in the lexical system) - عيد عبد الحق (Maalim, 2022)
There has been a lot of talk about the diversity and plurality of dialects of the same language, and it seems that this multiplicity is increasing even if we do not feel that, and this is only the result of social change taking place in the field and supported by mixing and interaction between different societies on the one hand, and civilization development on the other hand, which generates Over the years, the various dialects are imprinted with the characteristics of new societies resulting from overlap and friction, and saying that the dialects are multiplied does not mean their apparent variation at different levels, but rather it is just a notice that there are slight differences between them that may not go beyond some phonemic phenomena, or some vocabulary, hence the study of dialect A specific region includes in its content the study of the dialects adjacent, or sometimes even remote. In this article, I will touch upon one of these dialects, represented by the dialect of the Setif region among the elderly, in an attempt to read the lexical system of this group